Identifikasi Kebijakan Digitalisasi dan Ketimpangan Pendidikan (Studi Kasus Guru Sekolah Dasar Kecamatan Raba Kota Bima) - Munauwarah, Rahmadin; Achadi, Muh. Wasith (Lembaga Yasin AlSys, 2023)
Digitalization is one of the Indonesian government's efforts to equalize access to education and reduce the problem of the digital divide in the educational context. This article aims to explore the extent to which digitalization policies have helped teachers in elementary schools in Raba District, Bima City to improve access to and quality of education and overcome their digital disadvantages. The method used in this research is qualitative with a case study approach. The respondents of this study were 13 teachers from 4 elementary schools, 1 school principal, and 1 elementary school supervisor. Data was collected through in-depth interviews and documentation. The results of this study indicate that there are two aspects of education digitalization policies that directly affect respondents. The first is the digitization of educational policy communications. In this aspect, teachers experience accelerated access to information about education policies and information in general. Teachers have a better understanding of national education policies and are able to follow direct directions from the central government through available information channels. In the second aspect, namely the digitalization of the teaching and learning process, teachers have not utilized the digital facilities provided to maximize the learning process even though they are aware that the government provides these facilitie.